Evaluación del riesgo biológico por corto punzantes y salpicaduras de sangre y propuesta de un plan de prevención en trabajadores del centro de salud Latacunga área 1. - Garcia Macías, Carmina Alexandra (2016)
It is conducted a study of descriptive type, non-experimental, transverse to identify and evaluate the biological risk in workers of the health center Latacunga through the use of the methodology Biogaval in each of the services where there is risk for sharp and blood splashing. This group of professionals is constantly exposed to biological risk factor in their work environment, however it has been rarely studied and addressed as an indispensable component and generator of management systems of occupational health. Parameter have been established and implemented referred to the methodology about the present research work, focusing not only on the risk assessment but also in the identification of characteristics and specific aspects of the worker and their work activity, the objective of the biological agent identification by area of work and other variables that have a direct influence on the development of possible damage to the population object of study by the exposure to this risk.In order to achieve the stated objectives, the present research work includes the verification of previous studies similar to proposed, the analysis of each variable that makes up the Biogaval method. The information obtained from the present study shows that the Biogaval method, itself is a useful tool for the evaluation of biological risk factor. In addition it has been verified after the implementation of all the variables of the method, that areas where sharp is handled as well as blood splashing constitutes the area more intolerable for biological risk labor, evidencing further that for its control the adoption of correct hygiene measures, programs of prevention and health promotion and mechanisms of information and training to staff can drastically reduce the level of risk in each area of work of the staff object of study.